2008
DOI: 10.1016/j.nuclphysb.2008.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic measure and winding of random conformal paths: A Coulomb gas perspective

Abstract: We consider random conformally invariant paths in the complex plane (SLEs). Using the Coulomb gas method in conformal field theory, we rederive the mixed multifractal exponents associated with both the harmonic measure and winding (rotation or monodromy) near such critical curves, previously obtained by quantum gravity methods. The results also extend to the general cases of harmonic measure moments and winding of multiple paths in a star configuration.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…It sets up the martingale techniques needed for dealing with mixed moments. Section 3 uses them for the study of the complex one-point function (a) in (12), which is shown to obey a simple differential equation in complex variable z. This leads to Theorem 3.1, which establishes a closed form for this function along the integrability parabola R in the (p, q)-plane.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It sets up the martingale techniques needed for dealing with mixed moments. Section 3 uses them for the study of the complex one-point function (a) in (12), which is shown to obey a simple differential equation in complex variable z. This leads to Theorem 3.1, which establishes a closed form for this function along the integrability parabola R in the (p, q)-plane.…”
mentioning
confidence: 98%
“…This leads to Theorem 3.1, which establishes a closed form for this function along the integrability parabola R in the (p, q)-plane. Section 4 is concerned with the moduli one-point function (b) in (12), and more generally, with the SLE two-point function G(z 1 ,z 2 ). A PDE in (z 1 ,z 2 ) is derived for G(z 1 ,z 2 ), which yields a proof of Theorem 4.2 establishing closed form expressions for G for all (p, q) ∈ R. Section 4.4 deals with the generalization of the previous integrability results to the m-fold symmetric transforms f [m] , m ∈ Z \ {0}, of the whole-plane SLE map f .…”
mentioning
confidence: 99%
“…On the other hand this bounded number of Whitney squares can be in turn covered by a uniformly bounded number of connected Whitney squares in D. Thus also the ratios of distances of f (z), f (w), f (u), f (v) from the boundary are bounded by constants. It follows again from the distortion theorems (14) that also the ratios of the different f (·) are bounded, giving us the claim.…”
Section: An Estimate On the Green's Functionmentioning
confidence: 65%
“…Very near the curve, this distortion is given by unwinding the SLE curve back to zero. One can also think that this definition of winding gives the amount that a curve from the infinity needs to wind to access the point z. Asymptotically near the curve, this version of winding should coincide with the geometric winding up to some bounded constants [14].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…There are a number of other quantities related to the multifractal spectrum which have been computed either rigorously or non-rigorously. These include the winding spectrum (predicted in [DB02,DB08]), higher multifractal spectra depending on the derivative behavior on both sides of the curve (predicted in [Dup03]), the integral means spectrum (rigorous computations of different versions given in [BS09a, GMS17, DNNZ12, LY13, LY14]), the multifractal spectrum at the tip (computed in [JVL12]), and the boundary multifractal spectrum (computed in [ABJ15]).…”
Section: Overviewmentioning
confidence: 99%